The effectiveness of image-based media in enhancing essay writing skills of third-grade students at GUPPI Islamic Elementary School, Southwest Papua - Kadasa, Sumiati; Faizin, Muhamad; Yulianto, Ahmad (Universitas Ahmad Dahlan, 2025)
This study aims to improve the essay writing skills of third-grade students at SD Islam GUPPI, Southwest Papua, through the use of image-based learning media. Initial assessment showed an average writing score of 62.3, below the Minimum Completeness Criteria (70), indicating a gap between curriculum demands and students’ actual competence. Using a Classroom Action Research design with two cycles, this study involved 24 students and employed observation sheets, writing rubrics, and performance tests. Data were analyzed using paired t-tests and effect size measures. The results showed a significant improvement in students’ writing skills, increasing from 62.3 in the pre-cycle to 82.5 in the second cycle (t = 5.47, p < 0.05; Cohen’s d = 1.21). The findings support Bruner’s constructivist view that visual stimuli help students build meaning and organize ideas more effectively. The study concludes that image-based media is an effective strategy to enhance students’ imagination, motivation, and expressive ability in elementary writing instruction.